1961
DOI: 10.1172/jci104381
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties and the Geometry of the Lungs*

Abstract: The elastic properties of the lung are of primary importance to normal function. A definitive study of these properties entails the simultaneous measurement of pressure and volume under static conditions. A plot of the relationship between pressure and volume in the lungs results in a curve which is approximately linear in the middle part of the vital capacity. The retractive force in this limited part of the curve is a direct function of volume. Although elastic performance is a complex phenomenon, the balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1963
1963
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…From such studies it has been suggested that collagen is the major determinant of lung structure (13) and that elastin plays little role in lung elastic behavior (14). In contrast, the present study indicates that enzymatic attack of elastin is associated with marked architectural changes and altered elastic behavior of the lung.…”
Section: Introductioncontrasting
confidence: 42%
See 1 more Smart Citation
“…From such studies it has been suggested that collagen is the major determinant of lung structure (13) and that elastin plays little role in lung elastic behavior (14). In contrast, the present study indicates that enzymatic attack of elastin is associated with marked architectural changes and altered elastic behavior of the lung.…”
Section: Introductioncontrasting
confidence: 42%
“…Received for publication 14 May 1971 and in revised form 11 October 1971. prone to develop emphysema (1). Circulating leukocyte or alveolar macrophage lysosomes may provide the necessary proteolytic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present experiments during the inflation cycle agree with the find ings of several previous investigations [28,30,31] in which subpleural air spaces were observed by microscopy during changes in lung volume. At low lung volumes the subpleural spaces exhibited diameters of 200 to 300 //.m.…”
Section: Discussionsupporting
confidence: 93%
“…The separate functions of these fibrous proteins have been deduced from histological studies of their arrangement in the lung parenchyma (1)(2)(3) and from the mechanical behavior of elastin and collagen fibers dissected out from other tissues (4,5). Further knowledge has been gained Received for publication 6 November 1974 and in revzised forni 6 February 1975. by studying the effects of elastolytic and collagenolytic enzymes on lung structure and function (6)(7)(8). A different approach has been to give animals in a period of lung growth agents that inhibit the normal biosynthesis of collagen and elastin (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%